Cost-effectiveness of Enhanced Recovery Versus Conventional Perioperative Management for Colorectal Surgery. Issue 6 (December 2015) - Lee, Lawrence; Mata, Juan; Ghitulescu, Gabriela A.; Boutros, Marylise; Charlebois, Patrick; Stein, Barry; Liberman, A. Sender; Fried, Gerald M.; Morin, Nancy; Carli, Franco; Latimer, Eric; Feldman, Liane S.
Abstract : Objective: To determine the cost-effectiveness of enhanced recovery pathways (ERPs) versus conventional care for patients undergoing elective colorectal surgery. Background: ERPs for colorectal surgery are clinically effective, but their cost-effectiveness is unknown. Methods: A multi-institutional prospective cohort cost-effectiveness analysis was performed. Adult patients undergoing elective colorectal resection at 2 university-affiliated institutions from October 2012 to October 2013 were enrolled. One center used an ERP, whereas the other did not. Postoperative outcomes were recorded up to 60 days. Total costs were reported in 2013 Canadian dollars. Effectiveness was measured using the SF-6D, a health utility measure validated for postoperative recovery. Uncertainty was expressed using bootstrapped estimates (10, 000 repetitions). Results: A total of 180 patients were included (conventional care: n = 95; ERP: n = 95). There were no differences in patient characteristics except for a higher proportion of laparoscopy in the ERP group. Mean length of stay was shorter in the ERP group (6.5 vs 9.8 days; P = 0.017), but there were no differences in complications or readmissions. Patients in the ERP group returned to work quicker and had less caregiver burden. There was no difference in quality of life between the 2 groups. The cost of the ERP program was 153 per patient. Overall societal costs were lower in the ERP group (mean difference = −2985; 95% confidence interval, −5753 to −373). The ERP had a greater than 99% probability of cost-effectiveness. The results were insensitive to a range of assumptions and subgroups. Conclusions: Enhanced recovery is cost-effective compared with conventional perioperative management for elective colorectal resection. Abstract : Supplemental Digital Content is available in the text